Risk stratification with troponin I in patients undergoing myocardial revascularization surgery - Leal,João Carlos Ferreira (2003)
OBJECTIVE: To determine the immediate behavior and the prognostic value in terms of late survival of serum troponin I measurement in patients undergoing myocardial revascularization surgery with extracorporeal circulation. METHODS: We studied 88 random patients, 65 (73.8%) of the male sex, who underwent myocardial revascularization surgery with extracorporeal circulation. Troponin measurements were performed as follows: in the preoperative period, right after intensive care unit admission, and on the first and second postoperative days. Values below 0.1 nanogram per milliliter (ng/mL) were considered normal. The cut points for late prognostic assessment were 0.5 ng/mL; 1 ng/mL; 2.5 ng/mL; and 5 ng/mL. RESULTS: The serum troponin I levels were elevated on the first postoperative day, suggesting the occurrence of specific myocardial damage. Patients with a poor prognosis could be identified, because the serum levels above 2.5 ng/mL and 5 ng/mL in the postoperative period resulted, respectively, in mortality rates of 33% and 50% in a maximum 6-month follow-up. CONCLUSION: Troponin I values around 2.5 ng/mL in the postoperative period should call attention to the need for more aggressive diagnostic or therapeutical measures.